2013
DOI: 10.3109/02813432.2012.751695
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of antibiotic resistance and antibiotic prescribing in UTI treatment: A qualitative study among primary care physicians in Sweden

Abstract: Objectives. To improve education and information for general practitioners in relation to rational antibiotic prescribing for urinary tract infection (UTI), it is important to be aware of GPs’ views of resistance and how it influences their choice of UTI treatment. The aim of this study was to explore variations in views of resistance and UTI treatment decisions among general practitioners (GPs) in a county in Sweden. Design. Qualitative, semi-structured interviews were analysed with a phenomenographic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 26 publications
5
41
0
Order By: Relevance
“…One result was the importance of the knowledge level of the GP, also corroborated in a previous study [24]. The findings indicate that continuity is favourable for the relationship between GP and patient, but it is obvious from another study [25] that when patients do not get well, continuity is not sufficient.…”
Section: Discussionsupporting
confidence: 66%
“…One result was the importance of the knowledge level of the GP, also corroborated in a previous study [24]. The findings indicate that continuity is favourable for the relationship between GP and patient, but it is obvious from another study [25] that when patients do not get well, continuity is not sufficient.…”
Section: Discussionsupporting
confidence: 66%
“…They indicated their high awareness of the threat of antimicrobial resistance. A similar attitude among physicians was shown in several studies from Europe and the USA as well as among medical students from various European countries (Bjorkman et al, 2013;Dyar et al, 2013;. Data from England revealed that the awareness of antimicrobial resistance threat is higher among physicians practicing in hospitals and long term care than in an outpatient setting (Simpson et al, 2007).…”
Section: Discussionsupporting
confidence: 62%
“…Qualitative research conducted in Europe suggests that many prescribers do not believe resistance is a local issue affecting their patients, and instead largely ascribe treatment failure to viral etiology rather than to resistant bacteria . However, those prescribers who are concerned about antibiotic resistance tend to conform to guidelines more consistently than those who are less concerned . Hence, there is clearly a serious risk if prescribers do not listen to the alarm.…”
Section: The Public Health Professionals and Predicting A Post‐antimentioning
confidence: 99%
“…60 However, those prescribers who are concerned about antibiotic resistance tend to conform to guidelines more consistently than those who are less concerned. 61 Hence, there is clearly a serious risk if prescribers do not listen to the alarm. Literature on behavior change 62 suggests consistent messages from respected and influential leaders to be most effective at changing attitudes.…”
Section: The Public Health Professionals and Predicting A Post-antimentioning
confidence: 99%